PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PROGRAM PASAR MURAH - Nur Sichah; Ahmad Efendi (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This Community Service (PkM) activity was implemented in Jombong Hamlet, Paten Village, a farming community, to address a crucial economic imbalance where the selling price of local agricultural commodities sharply declined while staple food prices rapidly inflated. The main objective of the program was to economically empower the community through immediate price intervention. The methodology employed was Participatory Action Research (PAR), engaging local stakeholders in the planning and implementation of the action. The core intervention was the Subsidized Market Program (Pasar Murah), designed to provide primary commodities (rice, cooking oil, sugar) at controlled prices. Implementation and observation results demonstrated that the program successfully reduced the immediate financial burden on households and mitigated the scarcity of critical supplies. The high level of community participation affirmed that the Subsidized Market is a successful and relevant option for revitalizing economic resilience and restoring local purchasing power.